ХОР ҲӘМ ХОРТАНЫЎ ПӘНИН ОҚЫТЫЎДЫ ЗАМАНАГӨЙ ПЕДАГОГИКАЛЫҚ ТЕХНОЛОГИЯ ҲӘМ ИНТЕРАКТИВ УСЫЛЛАР ТИЙКАРЫНДА ШӨЛКЕМЛЕСТИРИЎ - Тажетдинова, С.М. (SCIENCE and SOCIETY, 2017)
The article deals with the description of methods of teaching modern pedagogical direction “Method of four degrees” and using new interactive methods “Work in mini-groups” in the process of teaching discipline of choirs.